Clinical Features and Outcome of Dogs with Epiglottic Retroversion With or Without Surgical Treatment: 24 Cases. (8th October 2015) - Skerrett, S.C.; McClaran, J.K.; Fox, P.R.; Palma, D.
Abstract : Background: Published information describing the clinical features and outcome for dogs with epiglottic retroversion (ER) is limited. Hypothesis/Objectives: To describe clinical features, comorbidities, outcome of surgical versus medical treatment and long‐term follow‐up for dogs with ER. We hypothesized that dogs with ER would have upper airway comorbidities and that surgical management (epiglottopexy or subtotal epiglottectomy) would improve long‐term outcome compared to medical management alone. Animals: Twenty‐four client‐owned dogs. Methods: Retrospective review of medical records to identify dogs with ER that underwent surgical or medical management of ER. Results: Dogs with ER commonly were middle‐aged to older, small breed, spayed females with body condition score (BCS) ≥6/9. Stridor and dyspnea were the most common presenting signs. Concurrent or historical upper airway disorders were documented in 79.1% of cases. At last evaluation, 52.6% of dogs that underwent surgical management, and 60% of dogs that received medical management alone, had decreased severity of presenting clinical signs. In dogs that underwent surgical management for ER, the incidence of respiratory crisis decreased from 62.5% before surgery to 25% after surgical treatment. The overall calculated Kaplan–Meier median survival time was 875 days. Conclusion and clinical importance: Our study indicated that a long‐term survival of at least 2 years can be expected in dogs diagnosed with epiglottic retroversion. The necessity of surgical management cannot be determined based on this data, but dogs with no concurrent upper airway disorders may benefit from a permanent epiglottopexy to alleviate negative inspiratory pressures.